A Generalist Protist Predator Enables Coexistence in Multitrophic Predator-Prey Systems Containing a Phage and the Bacterial Predator Bdellovibrio - Johnke, Julia; Baron, Maayan; de Leeuw, Marina; Kushmaro, Ariel; Jurkevitch, Edouard; Harms, Hauke; Chatzinotas, Antonis (Frontiers in Ecology and Evolution, 2017)
Complex ecosystems harbor multiple predator and prey species whose direct and indirect interactions are understudied. In particular, the combined effects of predator diversity and resource preference on prey removal are not known. To better understand the effect of interspecies interactions combinations of micro-predators – i.e. protists (generalists), predatory bacteria (semi-specialists), and phages (specialists) – and bacterial prey were tracked over a 72-hour period in miniature membrane bioreactors. While specialist predators alone drove their preferred prey to extinction, the inclusion of a generalist resulted in uniform losses among prey species. Most importantly, presence of a generalist predator enabled coexistence of all predators and prey. As the generalist predator also negatively affected the other predators we suggest that resource partitioning between predators and the constant availability of resources for bacterial growth due to protist predation stabilizes the system and keeps its diversity high. The appearance of resistant prey strains and subsequent evolution of specialist predators unable to infect the ancestral prey implies that multitrophic communities are able to persist and stabilize themselves. Interestingly, the appearance of BALOs and phages unable to infect their prey was only observed for the BALO or phage in the absence of additional predators or prey species indicating that competition between predators might influence coevolutionary dynamics.